2011
DOI: 10.1007/s10530-011-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an invasive reef-building polychaete on the biomass and composition of estuarine macroalgal assemblages

Abstract: Invasive species can transform ecological communities. Their profound effects may alter the sources and pathways of primary production. We investigated the effects of the reef forming polychaete Ficopomatus enigmaticus invasion on the biomass and distribution of estuarine macroalgae in a SW Atlantic coastal lagoon (Mar Chiquita, 37°40 0 S, 57°23 0 W, Argentina). Reefs built by this species serve as substrates for macroalgal development and furnish structures that modify physical and biological conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…Additionally, filter feeders are commonly considered ecosystem engineers because of the complex substrate structure they create, which explains the strong increase observed in the abundance of benthic invertebrates in invaded habitats (e.g. Higgins & Zanden, ; Bazterrica et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, filter feeders are commonly considered ecosystem engineers because of the complex substrate structure they create, which explains the strong increase observed in the abundance of benthic invertebrates in invaded habitats (e.g. Higgins & Zanden, ; Bazterrica et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, filter feeders are commonly considered ecosystem engineers because of the complex substrate structure they create, which explains the strong increase observed in the abundance of benthic invertebrates in invaded habitats (e.g. Higgins & Zanden, 2010;Bazterrica et al, 2012). Several studies have reported massive reductions in the coverage of submerged macrophytes within a few years of invasion by omnivores such as crayfish (e.g.…”
Section: Impacts Of Invasive Species From Different Trophic Positionsmentioning
confidence: 99%
“…The case of Ficopomatus enigmaticus , a serpulid widely dispersed around the world and with a long historical record of invasions, is a well-known example, because it can have dramatic impacts in invaded habitats building large, reef-like colonies in some coastal lagoons that cause major changes in benthic communities, especially in the Lake of Tunis (ten Hove and van den Hurk 1993) and the Mar Chiquita Lagoon, Argentina (Schwindt et al 2001, Luppi and Bas 2002, Bazterrica et al 2012). Rioja (1943) recorded, for the first time, Ficopomatus enigmaticus from Puerto Quequén, south of Mar del Plata, and now the species is widely distributed in the Mar Chiquita Lagoon, forming annular reefs and having several effects on the ecosystem and navigation of fishing boats in this lagoon-system (Schwindt et al 2001, Luppi and Bas 2002, Schwindt et al 2004a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the feeding activity of their individuals generates a strong top‐down control on phytoplankton, increasing benthic–pelagic coupling (Bruschetti, Bazterrica, Fanjul, Luppi, & Iribarne, 2011; Bruschetti, Luppi, Fanjul, Rosenthal, & Iribarne, 2008). Furthermore, reefs provide a hard substrate surface sustaining macroalgae settling and growth, inhibited on nearby sediment (Bazterrica, Botto, & Iribarne, 2012).…”
Section: Introductionmentioning
confidence: 99%